Water Productivity of Mustard Green (Brassica juncea L.) with Variation of Irrigation Systems - Nova Anika; Muh Kusmali; Harmiansyah Harmiansyah; Setyadi Gumaran; Ridwan Ridwan (The University of Lampung, 2024)
Drip irrigation and self-watering are two examples of irrigation technology improvements that employ effective and efficient watering methods. Water productivity may be used as a benchmark to compare irrigation efficiency and agricultural productivity. The purpose of this study was to assess mustard green's water productivity under conventional, drip, and self-watering irrigation systems. The effect of irrigation variation on mustard green growth was studied using a nonfactorial technique with a completely randomized design (CRD). The design has three treatments and six replications. This study examined the following variables: height, number of leaves, yield, irrigation water utilized, and water productivity of mustard green. The study found that mustard green plants require 0.69 mm/day of water in the vegetative phase, 2.83 mm/day in the generative phase, and 1.69 mm/day in the final phase. The use of different watering systems has a significant influence on mustard green's height and leaf number. Self-watering at 15 g/L provides the maximum water productivity for mustard green, followed by drip irrigation at 8.46 g/L and conventional irrigation at 7.69 g/L. Keywords: Drip irrigation, Mustard green, Self-watering irrigation, Water productivity